2005
DOI: 10.1111/j.1600-0722.2005.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of initial caries lesions on smooth surfaces by quantitative light‐induced fluorescence and visual examination: an in vivo comparison

Abstract: The aim of this clinical study was to compare the outcome of quantitative laser/light-induced fluorescence (QLF) and visual inspection (VI) for the detection of initial caries lesions on all maxillary and mandibular smooth surfaces in caries-risk adolescents. The subjects were 34 students, mean age 15 yr. A total of 879 buccal and 882 lingual surfaces were air-dried and visually examined at a magnification of x3.5. Fluorescence images of each smooth surface were captured with QLF\clin equipment, and QLF softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
1
21
0
3
Order By: Relevance
“…2 mm for demineralization, and the nail-varnished enamel blocks were then immersed in a demineralizing solution (12 m M CaCl 2 , 10 m M KH 2 PO 4 , 100 m M acetate, 100 m M NaCl, 50 m M lactate, 0.02% NaN 3 ; pH 4.5) at 37 ° C. The demineralization period was basically 7 days, but for less demineralized enamel blocks, the period was extended day by day up to 7 days. The degree of demineralization was checked using the QLF system in terms of average fluorescence loss ( ⌬ F) [Heinrich-Weltzien et al, 2005]. This enabled us to obtain 46 demineralized enamel blocks with a similar degree of demineralization.…”
Section: Tooth Sample Preparationmentioning
confidence: 99%
“…2 mm for demineralization, and the nail-varnished enamel blocks were then immersed in a demineralizing solution (12 m M CaCl 2 , 10 m M KH 2 PO 4 , 100 m M acetate, 100 m M NaCl, 50 m M lactate, 0.02% NaN 3 ; pH 4.5) at 37 ° C. The demineralization period was basically 7 days, but for less demineralized enamel blocks, the period was extended day by day up to 7 days. The degree of demineralization was checked using the QLF system in terms of average fluorescence loss ( ⌬ F) [Heinrich-Weltzien et al, 2005]. This enabled us to obtain 46 demineralized enamel blocks with a similar degree of demineralization.…”
Section: Tooth Sample Preparationmentioning
confidence: 99%
“…Initial studies have examined the detection of lesions on clinically susceptible teeth or patients and have claimed that the device detected more lesions than are visible clinically [Boersma et al, 2005]. It has also been reported that the methodology can detect and quantify the remineralization of such lesions over time [Kühnisch and Heinrich-Weltzien, 2004;Heinrich-Weltzien et al, 2005;Meller et al, 2006;Stookey, 2005].…”
mentioning
confidence: 99%
“…This method has been shown to be sensitive for the detection of early incipient lesions selin de Jong et al, 1995;Ando et al, 1997Ando et al, , 2001Ando et al, , 2004bAngmar-Mansson and ten Bosch, 2001;Shi et al, 2001;Tranaeus et al, 2001;Amaechi et al, 2003;Gonzalez-Cabezas et al, 2003;Heinrich-Weltzien et al, 2005;Stookey, 2005;Pretty, 2006;Pretty and Ellwood, 2007], but it is subject to confounding effects of saliva [Amaechi and Higham, 2002], drying time [Pretty et al, 2004], angulation [Buchalla et al, 2002;Ando et al, 2004a] and stain [Shi et al, 2001] among others factors [Heinrich-Weltzien et al, 2005]. Additionally, although QLF parameters (lesion depth expressed as ⌬ F and lesion volume expressed as ⌬ Q) have been shown to have a higher sensitivity when compared to other methods for detection of early caries lesions [Ferreira Zandoná et al, 2003] because the QLF analysis software detects any change in pixel values as demineralization, their specificity is greatly compromised.…”
mentioning
confidence: 99%